Gambling, the state and society in Thailand, c. 1800-1945 - Warren, James A. (New York : Routledge, 2013)
"Charts the development of gambling in Thailand and relates it to the development of Thai state and society, showing how gambling was a fundamental issue hugely affecting political developments. It considers the difference between law and how law is enforced, outlining how the Thai elite, though professing opposition to gambling, often both tolerated and profited from it, as did the police"--Provided by publisher.
Gambling and socio-economic change in nineteenth-century Siam -- Games, dens and players : gambling in nineteenth-century Thai society -- Gambling revenue and the creation of the modern Thai nation-state -- The Thai elite, anti-gambling and lawmaking -- The police and enforcement -- The judiciary, punishment and the prison -- The press and the Bangkok middle class -- Buddhism, the sangha and the silent majority -- The criminalization of vice : gambling policy in comparative perspective.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Gambling -- Thailand -- History; Electronic books